Effect of Remaining Venous Reservoir Blood Administration on Transfusion in Open Heart Surgery (Annals of Medical Research, 2021)
Aim: There is no consensus between different clinics about the usage of remaining blood in venous reservoir during coronary bypass surgery with cardiopulmonary bypass operation. Our prospective study, we aimed to research effects of the use of remaining blood in venous reservoir after cessation of cardiopulmonary bypass for patients undergoing coronary bypass surgery on drainage, need for blood and blood products, postoperative infection complications, duration of intensive care unit and total hospitalization time.
Keywords: Cardiopulmonary Bypass; Venous Reservoir; Coronary Bypass Surgery; Postoperative Hemorrhage.